A Review of Phytochemistry and Pharmacological Properties of Threatened Croton Species Used as Herbal Medicines in East Africa - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2018)
Some rare and threatened Croton species have a long history of medicinal usage in East Africa. The objective of this study was to review the phytochemistry and pharmacological properties of five Croton species that are threatened with extinction in East Africa but widely used as herbal medicines in the region. Information on medicinal uses, phytochemistry and pharmacological properties of C. alienus, C. dictyophlebodes, C. jatrophoides, C. megalocarpoides and C. talaeporos was obtained from databases such as Scopus, Web of Science, Science Direct, Google Scholar, PubMed, BioMed Central (BMC), Springerlink and Scielo. Other sources of information included scientific publications, conference proceedings, theses, books and book chapters obtained from libraries. Literature search revealed that the bark, fruits, leaves and roots of these five Croton species are commonly used as traditional medicines for gastro-intestinal disorders, colds and influenza, body pains and weaknesses and intestinal worms. Phytochemical compounds isolated from these species include alkaloids, anthraquinones, diterpenoids, esters, flavonoids, furanoditerpenoids, limonoids, methylcyclohexanes, phenolics, steroids, tannins and triterpenoids. Pharmacological studies indicate that these species have antifungal, anti-leishmanial and insect antifeedant activities. Preliminary phytochemical and pharmacological research done so far on Croton species is promising, but too general to corroborate some of the medicinal uses of the species.